Beaver dam analogues drive heterogeneous groundwater–surface water interactions. Issue 26 (27th October 2020) - Wade, Jeffrey; Lautz, Laura; Kelleher, Christa; Vidon, Philippe; Davis, Julianne; Beltran, Julio; Pearce, Casey
Abstract: Beaver dam analogues (BDAs) are a cost‐effective stream restoration approach that leverages the recognized environmental benefits of natural beaver dams on channel stability and local hydrology. Although natural beaver dams are known to exert considerable influence on the hydrologic conditions of a stream system by mediating geomorphic processes, nutrient cycling, and groundwater–surface water interactions, the impacts of beaver‐derived restoration methods on groundwater–surface water exchange are poorly characterized. To address this deficit, we monitored hyporheic exchange fluxes and streambed porewater biogeochemistry across a sequence of BDAs installed along a central Wyoming stream during the summer of 2019. Streambed fluxes were quantified by heat tracing methods and vertical hydraulic gradients. Biogeochemical activity was evaluated using major ion porewater chemistry and principal component analysis. Vertical fluxes of approximately 1.0 m/day were observed around the BDAs, as was the development of spatially heterogeneous zones of nitrate production, groundwater upwelling, and anaerobic reduction. Strong contrasts in hyporheic zone processes were observed across BDAs of differing sizes. This suggests that structures may function with size‐dependent behaviour, only altering groundwater–surface water interactions after a threshold hydraulic step height is exceeded. Patterns of hyporheic exchange and biogeochemical cycling around the studied BDAs resemble those around natural beaver dams, suggesting that BDAs may provide comparable benefits to channel complexity and near‐stream function over a 1‐year period. Abstract : Beaver dam analogues (BDAs) altered hyporheic exchange and created distinct spatial patterns of biogeochemical cycling within 1 year of their installation. Magnitudes of BDA‐induced exchange fluxes were closely linked to a threshold hydraulic step height. BDAs created moderate and heterogeneous hyporheic zone conditions and produced effects comparable to those of natural beaver dams.